BIBLIOMETRIC REVIEW: RESEARCH ON MATHEMATICAL LITERACY ABILITY IN MATHEMATICS LEARNING (1979-2023) - Abdurrahman Do. Muhamad Naser; Dadang Juandi (Pedagogy: Jurnal Pendidikan Matematika, 2023)
This study aims to look at the relevant previous research landscape related to mathematical literacy in mathematics learning from 1979 to 2023 using bibliometric analysis. Data were taken from the Scopus database of 578 and refined into 112 publications. Based on the results of the bibliometric analysis, it was found that 2022 would be the year for the most published articles, namely 12 articles. The trend of citations related to mathematical literacy in learning mathematics occurred in 2015 as many as 295 citations. South African countries are countries that publish articles related to mathematical literacy in learning mathematics with 26 publications and 20 collaboration links with other countries. Of the 112 journals that have published research related to this field, 46 of them have been published in Q1 journals. The focus of research related to literacy in learning mathematics is 1) gender and students; 2) numeracy; 3) mathematics education.